PENGARUH STRES KERJA TERHADAP PRESTASI KERJA KARYAWAN PADA PT. BUMI JAYA KABUPATEN TABALONG (p3m.stiatabalong.ac.id, 2022)
Every company definitely wants its employees to have achievements because having employees who excel can improve their performance. The aims of this study were (1) to find out whether work stress affects employee performance at PT. Bumi Jaya, Tabalong Regency. (2) To find out how much influence work stress has on employee performance at PT. Bumi Jaya, Tabalong Regency. This study uses a quantitative approach. The population in this study amounted to 301 people. The sampling technique used was purposive sampling, namely the technique of determining the sample with certain considerations, sampling based on special selection, the researcher made certain criteria for who was used as a sample of informants. The samples taken in this study were HRD, Ehs and Lab-AQC employees, totaling 34 people. Sources of data obtained by questionnaire and data documents or archives from PT. Bumi Jaya, Tabalong Regency. Data processing uses Generalized Structured Component Analysis (GSCA). Based on the results of hypothesis testing (1) work stress affects employee performance at PT. Bumi Jaya, Tabalong Regency. (2) The magnitude of the effect of work stress on employee performance at PT. Bumi Jaya Tabalong Regency by 52.5% and the remaining 47.5% is influenced by factors outside of this study. Keywords: working Stress and Job Performance